Income inequality and property crime in selected Southern and Eastern European countries - Buba, Saad; Ishak, Suryati; Habibullah, Muzafar Shah; Mohd Noor, Zaleha (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
This paper examines the impact of income inequality on the property crime by testing its effect using pooled mean group (PMG) estimator developed by Pesaran et al. (1999). Income inequality is specifically seen as the most noticeable feature of a bigger and more complex issue; less than 10 percent of the wealth in developed and developing countries is controlled by the poorest. Data from 14 emerging countries in the Southern and Eastern European regions were used to test and extend the income inequality and crime hypothesis. Variables such as the rule of law, unemployment, and education were also employed to examine their effects on property crime rate. The findings confirmed that the income inequality is positively associated with property crime rate. The rule of law, unemployment, and level of education also revealed a meaningful relationship with property crime rate in these regions.